Association of intraocular pressure‐related factors and retinal vessel diameter with optic disc rim area in subjects with and without primary open angle glaucoma - Zhang, Qing; Jan, Catherine; Guo, Chun Y; Wang, Feng H; Liang, Yuan B; Cao, Kai; Zhang, Zheng; Yang, Di Y; Thomas, Ravi; Wang, Ning L (Clinical & experimental ophthalmology, 2018)
Importance The data may support the notion that the intra‐ocular pressure (IOP)‐related factors and vascular factors were implicated concurrently in glaucomatous optic nerve damage. Background To study the association of intraocular pressure (IOP)‐related factors, IOP, trans‐lamina cribrosa pressure difference (TLCPD), cerebrospinal fluid pressure (CSFP) and retinal vessel diameters (RVD), central retinal arteriolar equivalent (CRAE), central retinal venular equivalent (CRVE) with neuro‐retinal rim area (RA). Design A population‐based, cross‐sectional study. Participants A total of 6830 people aged 30 years and over. Methods All participants underwent a comprehensive eye examination, fundus photograph‐based measurements of RVD and Heidelberg retinal tomogram (HRT) measurement of optic disc. Main Outcome Measures RA, CRAE, CRVE, IOP, body mass index (BMI), CSFP and TLCPD. Results Primary open‐angle glaucoma (POAG) was diagnosed using two separate methods: 67 from expert consensus, and 125 from the International Society of Geographical and Epidemiologic Ophthalmology (ISGEO) classification. After excluding of those with high myopia or without gradable HRT images, 4194 non‐glaucoma and 40 POAG were analysed for determinants of RA. On multivariable analysis determinants of reduced RA were POAG (P < 0.001), higher IOP (P = 0.03), higher refractive error (P < 0.01), longer axial length (P = 0.01), CRVE (P < 0.001), lower BMI (P = 0.015), older age (P < 0.001) smaller disc area (P < 0.001) and higher TLCPD (P = 0.03). When age and/or BMI were omitted from the model, reduced RA was also associated with lower CSFP (P < 0.001). Conclusions and Relevance Reduced RA is associated with narrow CRVE and higher IOP or lower CSFP. The data supports the concurrent role of IOP‐related and vascular factors in glaucomatous optic nerve damage.